MODIFIED ATMOSPHERE FOR THRIP DISINSECTION ON CUT LOTUS FLOWERS - S BUMROONGSOOK; M KILASO (My University, 2018)
In Thailand, lotus flowers are one of exportable products for flower trade industry.Common blossom thrip (Frankliniella schultzei) contamination on cut lotus flowers after harvest has been a major problem for export.F. schultzei is a quarantine insect pest.Modified atmospheres (MA) without oxygen content are considered an alternative to methyl bromide fumigation to control thrips.MA treatment has been used to control insect pests in agricultural product commodities.Different combinations of carbon dioxide, nitrogen, ozone levels, and treatment times were used to effect mortality of the common blossom thrips and postharvest quality of cut lotus flowers.Exposure to different concentrations of O 3 fumigation for 2 days could kill almost all F. schultzei (100% of larvae and ≥ 96% of adults).However, a concentration of 50-250 ppm of O 3 could not control F. schultzei on lotus flowers completely.O 3 fumigation caused color change in lotus flowers.High concentrations of O 3 (≥ 150 ppm) had a negative effect on the visual quality of lotus flowers.The results revealed that thrips mortality increased with increased CO 2 level and storage time.100% CO 2 caused 100% mortality of both adults and larvae of F. schultzei when there was a 6-h exposure.MA were more effective in disinfecting of thrips on cut lotus flowers after 9 h fumigation to ≥ 50% CO 2 caused complete mortality to F. schultzei.There was not much difference in lotus color in response to atmosphere modified by a combination of CO 2 and N 2 .Therefore, CO 2 disinfestation treatment has the potential to be developed commercially as an alternative postharvest control for common blossom thrips on lotus flowers.
Keywords: Flowering Plant Growth and Cultivation